Soil-transmitted helminthiasis among school-aged children in selected primary schools in southwest Nigeria: A cross-sectional study - Femi Awotokun; Oluyomi Abayomi Sowemimo; Ruqayah Olawoyin; Ashiat Alaba Adeleke (Health for All Nations, 2024)
This cross-sectional study was conducted to determine the prevalence and intensity of infection of soil-transmitted helminths among school-aged children in Ife Central and Ife East Local Government Areas, Osun State, Nigeria.Fresh stool samples were collected from 324 pupils, comprising 162 males and 162 females (aged 5-12 years). The preserved fecal samples were processed using a modified Kato-Katz technique. Data were analyzed using the Statistical Package for Social Sciences (SPSS) version 20. Of the 324 fecal samples examined, 79 (24.4%) tested positive for helminth eggs. The eggs were identified as Ascaris lumbricoides, with a prevalence of 22.2%, and hookworm; with a prevalence of 3.7%. Double infections were observed in 5 (1.5%) pupils. Private schools had a slightly higher prevalence (24.7%) than did public schools (24.1%). Sex-related prevalence was higher among males (25.9%) than females (22.8%), and no significant difference existed in the prevalence level between the sexes (p > 0.05).This study concluded that STH infection remains a public health risk among children in the study area.